2012
DOI: 10.7314/apjcp.2012.13.11.5805
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Treatment Compliance and Nutritional Outcomes among Patients with Nasopharyngeal Carcinoma with and without Percutaneous Endoscopic Gastrostomy during Chemoradiation

Abstract: Aims: The study aimed to compare treatment compliance and nutritional outcomes in nasopharyngeal carcinoma (NPC) patients during chemoradiation. Methods: Clinical information of patients with NPC that underwent chemoradiation during 2004-2009 were retrieved from the hospital database and retrospectively reviewed. Patients were categorised into a prophylactic percutaneous endoscopic gastrostomy (PPEG) group and a non-PPEG group. Clinical information including treatment compliance, weight, haematological and ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Radiotherapy alone has been the first curative treatment of NPC and the concomitant chemoradiotherapy appears to be new treatment modality for locoregionally advanced NPC [ 33 ]. During treatment, patients may suffer from many acute and late-onset complications such as mucositis, dysphagia, nausea, and vomiting during therapy and these symptoms could lead to dehydration, undernutrition and impaired immune functions[ 34 ]. Thus, it is important that we provide patients with accurate information about the magnitude of benefit and the balance against excessive chemoradiotherapy toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy alone has been the first curative treatment of NPC and the concomitant chemoradiotherapy appears to be new treatment modality for locoregionally advanced NPC [ 33 ]. During treatment, patients may suffer from many acute and late-onset complications such as mucositis, dysphagia, nausea, and vomiting during therapy and these symptoms could lead to dehydration, undernutrition and impaired immune functions[ 34 ]. Thus, it is important that we provide patients with accurate information about the magnitude of benefit and the balance against excessive chemoradiotherapy toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss is a common side effect during chemotherapy or radiotherapy in patients with head and neck cancer, especially NPC; the average weight loss in patients is reported to be 5.5-12.3 kg, and 86% of patients lose >10% body weight 20 - 22 . In our primary cohort, 95.9% patients had experienced different extents of weight loss, with an average of 5.7 kg, which was similar to that in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our meta-analysis of 9 subsets, we confirmed that WTratio was an independent prognostic factor for DMFS, and the funnel plot for DMFS indicated no obvious publication bias. As such, nutritional management such as a prophylactic percutaneous endoscopic gastrostomy 22 might improve survival and quality of life in for patients with late-stage cancer. Combined with smoking, pre-DNA level, and N group, we developed a new nomogram model for DMFS, which showed a favorable predictive accuracy of 4-year distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition support for patients undergoing CCRT was confirmed to be an important measure for maintaining both energy and protein 35. Multiple studies demonstrated that PEG tubes can ameliorate malnutrition in patients with HNC undergoing radiation therapy 14,15,36,37…”
Section: Discussionmentioning
confidence: 99%
“…Those literatures suggested that prophylactic PEG tube placement could improve treatment tolerance, prevent weight loss and malnutrition, and improve overall survival for HNC patients. Besides, only one study specially evaluated the benefit of reducing weight loss from the placement of PEG tubes for NPC patients during CRT 15. But that study did not evaluate the tolerance of concurrent chemotherapy and other benefits of nutrition status from the PEG tube for LA-NPC patients during CCRT.…”
Section: Introductionmentioning
confidence: 99%